PERANCANGAN SISTEM INFORMASI ADMINISTRASI DAN MONITORING TRANSAKSI BERBASIS WEB MOBILE - Irawan Candra (Semantik, 2011)
This information system will further simplify the processes of access to information by using mobile technology. So that access to information will be faster, more accurate and reduce the cost of the required and pressing traffic data transmissions. This system design using UML (Unified Modeling Language), which include monitoring of daily transactions, monthly transactions and the previous month, the input of deposit as a ceiling for payment of service or unblok point and block the transaction. Applications that produced runs on mobile devices or Smart Phone that already has a browser.Keywords: mobile, browser, UML